BreadTrail: from farm to fork - Jardine, Darien; Sharma, Nirvan; Ramjattan, Reshawn (Technical Centre for Agricultural and Rural Cooperation, 2018)
BreadTrail, an app created by Darien Jardine, Nirvan Sharma and Reshawn Ramjattan, makes introducing reliable and incorruptible traceability to the supply chain secure and scalable while providing benefits to everyone involved from farmer to customer.